Oculomotor Paresis and Basilar Aneurysm - J Gordon Millichap (Pediatric Neurology Briefs, 1992)
The clinical and pathologic findings in a 10 month old girl with congenital heart diseasewho died after rupture of a congenital distal basilar artery aneurysm are reported from the University of Connecticut Health Center, Farmington, CT and the Children’s Hospital of Philadelphia, PA.